Profiles of mental development of children with tuberous sclerosis - L. A. Troitskaya; N. E. Malakhova; A. D. Rodionova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Tuberous sclerosis complex (TSC) is a peculiar genetic disorder that is associated with prenatal central nervous system damage that impairs child’s post-natal mental development. Aim of the study is to define how severity of TCS affects the peculiarities of 7 to 12 years old children’s mental development. The study examines ways for the application of psychological methods to diagnose this disease in children. «Profiles of psychological developments» that included assessment of substantial and constructive activities, games and play activities, speech, communication, emotional-volitional and motor areas, and self-care were created based on the examination of 24 children. A distinct qualitative variability of mental development that ranged from the norm to grave underdevelopment including in rare cases intellectual and behavioral regression was identified. Timely determination of children’s psychological status with tuberous sclerosis was shown to be necessary to plan and implement correctional psychological, pedagogical, social assistance, and serve as one of the markers contributing to severity of the disease.